2020
DOI: 10.21873/anticanres.14425
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Radiotherapy for Glioblastoma Multiforme – The Impact on Disease Outcome

Abstract: Background/Aim: To study the changes of glioblastoma multiforme during chemoradiotherapy (CRT) and to evaluate the impact of changes on dosimetry and clinical outcomes. Patients and Methods: Forty-three patients underwent volumetric imaging-based replanning. Prognostic factors and gross tumor volume changes in relation to overall survival and the effect of adaptive replanning were statistically analyzed. Results: Patients with total tumor removal, with shorter time to CRT (<27 days), with methylated O-6 methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The majority of patients with grade III or IV gliomas and selected patients with grade II gliomas are scheduled for radiochemotherapy, mainly following neurosurgical resection (4)(5)(6). This situation may produce significant emotional distress for the patients due to fears regarding the treatment procedure, potential side effects, and unsatisfactory treatment outcomes including progression or recurrence of the glioma (7)(8)(9)(10)(17)(18)(19). These fears may lead to sleep problems that can significantly impair the patients' quality of life (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with grade III or IV gliomas and selected patients with grade II gliomas are scheduled for radiochemotherapy, mainly following neurosurgical resection (4)(5)(6). This situation may produce significant emotional distress for the patients due to fears regarding the treatment procedure, potential side effects, and unsatisfactory treatment outcomes including progression or recurrence of the glioma (7)(8)(9)(10)(17)(18)(19). These fears may lead to sleep problems that can significantly impair the patients' quality of life (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Our observations support the previous notions that locally and distally recurrent glioblastomas exhibit different evolutionary patterns, in particular, linear and branching evolutions, respectively, and that the location of tumor recurrence helps predict the evolutionary pattern in glioblastoma. Concurrent chemoradiation therapy exerts a powerful selective pressure, and chemo-and radio-resistant cell clones contribute to the development of glioblastoma recurrence (7,(40)(41)(42)(43)(44). Common ancestral cells are likely to pre-exist in the untreated primary glioblastoma and are positively selected by chemoradiation therapy (18,41,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Further research found that (1) during the implementation of ART technology, the degree of changes in tumor regression is closely related to the dose range of the irradiation target area and the irradiation dose of adjacent normal tissues and organs [7]. (2) e degree of tumor regression varies among patients during treatment, and some patients have no significant changes in tumor volume during the pre-course and mid-course treatment (possibly due to radiation resistance) [8]. In view of this, some scholars believe that these patients may not benefit from ART, and may not need ART at least in the first and middle course of treatment.…”
Section: Introductionmentioning
confidence: 99%